PENGARUH PENDAPATAN, PENGELOLAAN ZAKAT, RELIGIUSITAS, KUALITAS LAYANAN TERHADAP MINAT SESEORANG DALAM MEMBAYARKAN ZAKAT DI BAZNAS KOTA BLITAR - Fany Caesar Rio Kurniawan (Jurnal Ilmiah Mahasiswa FEB, 2019)
The influence of income, zakat management, religiosity, service quality on the interest of a person giving zakat al- Mal in Blitar City. This research uses quantitative research methods. The analysis technique used is multiple linear regression analysis. The data obtained are primary data from distributing questionnaires directly to respondents. The results of this study indicate that the variable income, zakat management, religiosity, service quality has a significant effect on one's interest in paying zakat al-Mal in Blitar City.Key words : Income, Trust, Zakat, BAZNAS